Two Main Perspective Analysis of Human Capital Management in Fashion MSMes Business Development (Study on Mix Outfit Medan) - Aqilah Dina Nafisah; Nana Dyki Dirbawanto (Journal of Finance and Business Digital, 2023)
Efficient human resource governance ensures smooth commercial growth within the company. Apart from that, to achieve a growing business, two main perspectives are needed in implementing business development. The aim of this research is to examine the impact of the two main perspective on human capital management on business development as well as the influence of the two main perspective on business development in Mix Outfit MSMEs. This research uses descriptive qualitative methodology. This research uses data collection approaches such as interviews, observation, documentation studies, and triangulation. The findings show that Mix Outfit in its business activities has implemented a two main perspective. However, this was less effective, because it was found that there were ongoing problems arising from practices in implementing the two main perspective concept.